Drug survival of adalimumab in patients with rheumatoid arthritis over 10 years in the real-world settings: high rate remission together with normal function ability. Issue 11 (November 2016) - Iannone, Florenzo; Sinigaglia, Lugi; Favalli, Ennio; Sarzi-Puttini, Piercarlo; Atzeni, Fabiola; Caporali, Roberto; Codullo, Veronica; Ferraccioli, Gianfranco; Gremese, Elisa; Carletto, Antonio; Giollo, Alessandro; Govoni, Marcello; et al.
Abstract The purpose of the study was to estimate the clinical profile of naïve biological patients with rheumatoid arthritis (RA) starting adalimumab through 3-year calendar periods and their clinical outcomes such as drug survival and global clinical disease control (GCDC). RA patients starting adalimumab as first biological drug between 2003 and 2012 were subdivided in 3-year calendar periods. Survival on therapy was estimated using the Kaplan-Meier analysis. One and 2-year clinical response was assessed by calculating percentage of patients attaining GCDC (28-joint Disease Activity Score (DAS28) ≤ 2.6 + Health Assessment Questionnaire (HAQ) ≤ 0.5), low disease activity (DAS28 ≤ 3.2), remission (DAS28 ≤ 2.6) and good European League Against Rheumatism (EULAR) response. Multivariate regression models were used to assess baseline predictors of drug discontinuation or achievement of clinical remission. We recruited 1695 RA patients. Overall drug persistence at 3 years was 40.6 %, while the global rate of nonswitching patients was 54.7 %. Compared to 2003–2005, initiators in more recent years had a significantly lower 3-year crude drug retention rate (log rank, p  < 0.0001) and a significantly higher rate of switching to alternative biologics (log rank, p  < 0.0001). No difference in adverse events or effectiveness rate among the calendar periods was found. A substantial proportion of patients (up to 27 %) achieved GCDC at 2 years, regardless of the calendar period. In real-life setting, RA patients starting adalimumab in more recent years had a higher rate of drug discontinuation not related to ineffectiveness or side effects but to switching, probably due to a wider availability of biologics. A meaningful proportion of patients attained GCDC without any difference across calendar periods.